2011
DOI: 10.1007/s13224-011-0094-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxidative Stress and Antioxidant Defence in Subjects of Preeclampsia

Abstract: Objectives To evaluate the parameters of oxidative stress and anti oxidant defense in preeclampsia and thereby find any etiological correlation. Methods Study was carried out on pregnant and non pregnant women attending or admitted in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 8 publications
2
19
0
1
Order By: Relevance
“…This result is similar to many studies like study by Gohil J. T. et al, Jyoti Dave et al and Sadanand Patil et al 11,12,13 Correlation of MDA was studied with systolic and diastolic blood pressure and a significant positive correlation between MDA and systolic (r=0.9950, p value 0.0050) and diastolic (r 0.9916, p value 0.0084) blood pressure was observed. A significant positive correlation was also found by Shikha Saxena et al between serum MDA level and systolic (r=0.567, p <0.001) and diastolic(r=0.443, p <0.001) blood pressure.…”
Section: Discussionsupporting
confidence: 90%
“…This result is similar to many studies like study by Gohil J. T. et al, Jyoti Dave et al and Sadanand Patil et al 11,12,13 Correlation of MDA was studied with systolic and diastolic blood pressure and a significant positive correlation between MDA and systolic (r=0.9950, p value 0.0050) and diastolic (r 0.9916, p value 0.0084) blood pressure was observed. A significant positive correlation was also found by Shikha Saxena et al between serum MDA level and systolic (r=0.567, p <0.001) and diastolic(r=0.443, p <0.001) blood pressure.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, MDA was significantly elevated in the PE group. High oxidative stress has been found in both human and animal studies, indicating its potential role in the pathophysiology of PE . Free radicals were also reported to cause cellular dysfunction, oxidative damage of biomolecules and endothelial dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…High oxidative stress has been found in both human and animal studies, indicating its potential role in the pathophysiology of PE. 46 Free radicals were also reported to cause cellular dysfunction, oxidative damage of biomolecules and endothelial dysfunction. 47 In this study, VitD supplementation significantly lowered plasma MDA level, thus reducing the oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The condition is characterized by new‐onset hypertension and proteinuria after 20 weeks of pregnancy [2]. Several studies have demonstrated a causal relationship between oxidative stress and the pathophysiology of pre‐eclampsia [3,4].…”
Section: Introductionmentioning
confidence: 99%